Influence of the Molecular Weight of PEG on the Polymer/Salt Phase Diagrams of Aqueous Two-Phase Systems - Kamila Wysoczanska (2016)
Binodal data for systems composed by polyethylene glycol (PEG) (4000, 6000, or 8000) and salt (potassium citrate, potassium sodium tartrate) were obtained using the cloud point method, at T = 298.15 K. Merchuk equation was applied for the fitting of binodal curves. Tie-lines for systems of PEG (4000, 6000)-potassium citrate and PEG (4000, 6000, 8000)-potassium sodium tartrate were determined by electrical conductivity and lyophilization, and correlated using Othmer-Tobias and Bancroft equations, to verify the reliability of the measured tie-lines. Data were compared with that of previous studies reported in the literature, giving an indication of which system is more efficient in terms of separation, taking into account possible combinations of salt's cations and PEGs of different molecular weight chosen for ATPS.